A multi-scale biomechanical model based on the physiological structure and lignocellulose components of wheat straw. (20th November 2015) - Chen, Longjian; Li, Aiwei; He, Xueqin; Han, Lujia
Highlights: A multi-scale biomechanics model of wheat straw was developed. The model considered the physiological structure and lignocellulose components. The model provided closed-form prediction of straw biomechanics behavior. The effect of lignocellulose components on biomechanics behavior was analyzed. Abstract: Biomechanical behavior is a fundamental property for the efficient utilization of wheat straw in such applications as fuel and renewable materials. Tensile experiments and lignocellulose analyses were performed on three types of wheat straw. A multi-scale finite element model composed of the microscopic model of the microfibril equivalent volume element and the macroscopic model of straw tissue was proposed based on the physiological structure and lignocellulose components of wheat straw. The tensile properties of wheat straw were simulated by ANSYS software. The predicted stress–strain data were compared with the observed data, and good correspondence was achieved for all three types of wheat straw. The validated multi-scale finite-element (FE) model was then used to investigate the effect of the lignocellulose components on the biomechanical properties of wheat straw. More than 80% of stress is carried by the cellulose fiber, whereas the strain is mainly carried by the amorphous cellulose.